Assessing Communication during Remote Follow-Up of Users with Pacemakers in Norway: The NORDLAND Study, a Randomized Trial - Daniel Catalan-Matamoros; Antonio Lopez-Villegas; Knut Tore Lappegård; Remedios Lopez-Liria (International Journal of Environmental Research and Public Health, 2020)
As effective communication is a key ingredient for the provision of quality healthcare services, this study aimed to explore the communication experiences in the remote monitoring of older adults with a pacemaker. The study was based on a non-masked randomized observational design. The Healthcare Communication Questionnaire and in-depth interviews were conducted for data collection. A total of 49 patients participated in the study. The study findings reveal overall positive communication experiences by pacemaker users in remote monitoring with no significant differences from users in hospital monitoring. The remote option is perceived as safe and convenient, and communicating with the clinicians from home is considered comfortable and confidential. The study provides insights into the content of communication experiences in telehealth and practical implications in healthcare contexts. In a world that increasingly relies on remote communication, it is crucial to match technologies to patient needs and assess communication with patients. This will ensure the success of new models of care and establish appropriate criteria for the use of telehealth services. These criteria are all relevant in the implementation of health technology in the future as a part of effective patient-centered care.